2010
DOI: 10.4006/1.3397803
|View full text |Cite
|
Sign up to set email alerts
|

An explanation for the cosmological redshift

Abstract: A new theoretical model is presented which accounts for the cosmological redshift in a static universe. In this model the photon is viewed as an electromagnetic wave whose electric field component causes oscillations in deep space free electrons which then reradiate energy from the photon, causing a redshift. The predicted redshift coincides with the data of the Hubble diagram. The predicted redshift expression allows for the first time distance measurements to the furthest observable objects, without having t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In Mamas' model the photon is viewed as an electromagnetic wave whose electric field component causes oscillations in deep space free electrons which then re-radiate energy from the photon, causing a red-shift. The predicted red-shift coincides with the data of the Hubble diagram [105].…”
Section: Deep Space Electronssupporting
confidence: 86%
“…In Mamas' model the photon is viewed as an electromagnetic wave whose electric field component causes oscillations in deep space free electrons which then re-radiate energy from the photon, causing a red-shift. The predicted red-shift coincides with the data of the Hubble diagram [105].…”
Section: Deep Space Electronssupporting
confidence: 86%
“…All the studies of Saalmann and Rost, 14 Kim et al, 15 and Mamas 12 have shown that there is energy transfer in the interaction process of photons with massive particles. It is realized here that all massive particles, including atoms and molecules, are possible to be affected by photons in deep space.…”
Section: A the Densities Of Photons And Massive Particlesmentioning
confidence: 97%
“…Although Zwicky objected to the Doppler effect interpretation of cosmological redshift, the tired light hypothesis was vague on physical mechanics, so few people took the hypothesis seriously. But there have been a few people contemplating tired light, keenly working to find the physical mechanics thereof, without success [5][6][7][8][9][10][11]. The physical mechanics of tired light was not clearly described until 2013 when M. Shao published his paper.…”
Section: The History Of "Tired Light" Theorymentioning
confidence: 99%